Potential of Cultural Heritage Sites for Introduction of Global Citizenship Education in Kazakhstan (International relations and international law Journal, 2019)
Global citizenship is one of the most important directions among actual activities of the United Nations Educational, Scientific and Cultural Organization in field of education. Importance of the global citizenship education is highly important in view of the Sustainable Development Goals that were adopted by the United Nations by 2015. In the Republic of Kazakhstan this concept remains new and currently understudied. In this regard the aim of present article is its brief presentation, as well as demonstration of the ways, how the cultural heritage sites on the territory of our country may contribute to wider inclusion of global citizenship education in the national education system. From the methodological point of view present article reviews such issues as description of the international significance of the global citizenship education, as well presentation of the latest studies of this questions that were taking place in the Republic of Kazakhstan. It concludes by the underlining of the clear need of introduction of the reviewed issue in the Kazakhstan’s educational system and the high potential of the cultural heritage sites of RK for their complementing demonstration to the students. Practical important of present brief description is to first of all demonstrate the most actual initiatives for studies of the global citizenship education on the international and national level.Key words: education; global citizenship; sustainable development goals; UNESCO.